PRE-NEOPLASTIC AND NEOPLASTIC CHANGES IN BRONCHIAL EPITHELIUM OF PATIENTS WITH SQUAMOUS CELL LUNG CANCER AND LUNG ADENOCARCINOMA - O. V. Pankova; V. M. Perelmuter; S. A. Tuzikov; Ye. V. Denisov (Бюллетень сибирской медицины, 2014)
The data on modern views on the problem of pre-cancerous changes (epithelial hyperplasia, squamous metaplasia, preneoplasia (dysplasia I) and neoplasia (dysplasia II-III) when squamous cell cancer and adenocarcinoma of the lung are summarizes in the present review. Atypical adenomatous hyperplasia, which is considered precancerous process for adenocarcinoma of the lung, due to the rare occurrence in the review is not considered. The attention is focused on the classification of morphological characteristics of precancerous changes in respiratory epithelium. The analysis of frequency and reversibility of preand neoplastic changes in bronchial epithelium. We discuss the connection between the nature of the changes of respiratory epithelium in the bronchi, developing simultaneously with squamous cell cancer or adenocarcinoma of the lung, with tumour progression.